Interferon-β-1a Inhibition of Severe Acute Respiratory Syndrome–Coronavirus 2 In Vitro When Administered After Virus Infection. (19th June 2020) - Clementi, Nicola; Ferrarese, Roberto; Criscuolo, Elena; Diotti, Roberta Antonia; Castelli, Matteo; Scagnolari, Carolina; Burioni, Roberto; Antonelli, Guido; Clementi, Massimo; Mancini, Nicasio
Abstract: The ongoing coronavirus disease 2019 pandemic has forced the clinical and scientific community to try drug repurposing of existing antiviral agents as a quick option against severe acute respiratory syndrome–coronavirus 2 (SARS-CoV-2). Under this scenario, interferon (IFN) β-1a, whose antiviral potential is already known, and which is a drug currently used in the clinical management of multiple sclerosis, may represent as a potential candidate. In this report, we demonstrate that IFN-β-1a was highly effective in inhibiting in vitro SARS-CoV-2 replication at clinically achievable concentration when administered after virus infection. Abstract : Interferon β-1a hampers severe acute respiratory syndrome–coronavirus 2 replication in a Vero E6 infection model when administered after virus infection in a dose-dependent manner. This observation could be useful in the set-up of clinical trials.